Contemporary Management - Waddell, Dianne; Devine, Jennifer; Jones, Gareth R.; George, Jennifer M. (Boston McGraw-Hill, 2009)
Presents a fresh and humane view of the manager in the workplace. This non-prescriptive text explores the manager as a person, rather than an institution, with values and ethics. Waddell, Deakin University, and Devine, Edith Cowan University.
Include Illustrations, Glossary and Index.
Keywords: Management -- Executive ability